2011
DOI: 10.1371/journal.pone.0022372
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal-Dependent Spatial Memory in the Water Maze is Preserved in an Experimental Model of Temporal Lobe Epilepsy in Rats

Abstract: Cognitive impairment is a major concern in temporal lobe epilepsy (TLE). While different experimental models have been used to characterize TLE-related cognitive deficits, little is known on whether a particular deficit is more associated with the underlying brain injuries than with the epileptic condition per se. Here, we look at the relationship between the pattern of brain damage and spatial memory deficits in two chronic models of TLE (lithium-pilocarpine, LIP and kainic acid, KA) from two different rat st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
109
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 68 publications
23
109
3
1
Order By: Relevance
“…Similar to the descriptions from previous reports, the seizures were characterized by brief tonic-clonic episodes with forelimb automatisms with rearing and falling [28]. On post-SE day 72, spontaneous EEG seizures were frequently observed in rats subjected to kainic acid.…”
Section: Effects Of Amd3100 On Spontaneous Eeg Seizures In Chronic Tlesupporting
confidence: 83%
“…Similar to the descriptions from previous reports, the seizures were characterized by brief tonic-clonic episodes with forelimb automatisms with rearing and falling [28]. On post-SE day 72, spontaneous EEG seizures were frequently observed in rats subjected to kainic acid.…”
Section: Effects Of Amd3100 On Spontaneous Eeg Seizures In Chronic Tlesupporting
confidence: 83%
“…However, its mRNA expression was significantly reduced at 2 nd and 3 rd weeks, when compared to the first week of SE induction ( † † † p < 0.001). The mRNA expressions of p75NTR and pro-NGF were normalized to GAPDH and were expressed as mean ± SD, n = 4. which is consistent with previous published reports [50][51][52] that demonstrated SE induction is associated with decreased anxiety in the elevated plusmaze, as evidenced by longer time spent and higher number of entries in arms. Similar to our finding, Detour and colleagues [50] found that in the elevated plus maze, epileptic rats exhibited a significant higher number of entries and the time spent in open arms, suggesting a reduction in the anxiety-related behavior.…”
Section: Discussionsupporting
confidence: 94%
“…Our data showed a reduction of learning acquisition; however it was only a transient reduction in water maze task. One study demonstrated a prominent reduction of memory in Sprague dawley but not Wistar rats (28), which shows strain dependency. Another study revealed that memory impairment is more probably related to lesion comorbidity rather than epilepsy itself (28).…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated a prominent reduction of memory in Sprague dawley but not Wistar rats (28), which shows strain dependency. Another study revealed that memory impairment is more probably related to lesion comorbidity rather than epilepsy itself (28). Retrieval data demonstrated a delayed impairment, one week later, on the time of probable structural lesion.…”
Section: Discussionmentioning
confidence: 99%